Seismic Performance Evaluation of Buried Sewage Collection Pipelines - Abolfazl Rahimi; Mohammad Rezaii (Shock and Vibration)
One of the systems which is damaged because of earthquake is an urban wastewater network. In this paper, it is tried to study the damages occurred on urban wastewater networks in a selected network. The most important definitions by the network about some branches of the wastewater network and relevant reformations are studied. Then, the function of pipeline networks buried by the previous earthquake is studied and also it is proceeded about the research studies done regarding the relationships dominant on susceptibility in which some of the mentioned relationships are studied. The statistical society of some methods used in this research is studied, and the software applied in this part is introduced. Finally, the data of the output results are analysed in which the results obtained by this research are including the output drawings of the software GIS that demonstrate the occurred damages in applied and clear way. Some suggestions for using the aforesaid results by the researchers and authorities, especially disaster headquarter, have been presented. The results of this study showed that the assumptions and also the modelling process have handled the simulation well and this process is an effective method in decision making.